Eastern Caribbean Currency Union : Staff Report for the 2004 Regional Surveillance. (IMF Staff Country Reports; Country Report ;, 2004)
The staff report for the 2004 Regional Surveillance on the Eastern Caribbean Currency Union (ECCU) focuses on the economic developments and near-term prospects. The fiscal position of the governments in the region has deteriorated sharply in recent years and resulted in a marked increase in public sector debt. Efforts in the region have focused on strengthening the supervisory and regulatory regimes in both the domestic banking sector and the offshore financial sector. Enhanced regional cooperation could also help broaden markets and provide opportunities to achieve economies of scale.